Depth of Solute Generation Is a Dominant Control on Concentration‐Discharge Relations. Issue 8 (20th August 2020) - Botter, M.; Li, L.; Hartmann, J.; Burlando, P.; Fatichi, S.
Abstract: Solutes in rivers often come from multiple sources, notably precipitation (above) and generation from the subsurface (below). The question of which source is more influential in shaping the dynamics of solute concentration cannot be easily addressed due to the general lack of input data. An analysis of solute concentrations and their dependence on discharge across 585 catchments in nine countries leads us to hypothesize that both the timing and the vertical distribution of the solute generation are important drivers of solute export dynamics at the catchment scale. We test this hypothesis running synthetic experiments with a tracer‐aided distributed hydrological model. The results reveal that the depth of solute generation is the most important control of the concentration‐discharge (C‐Q) relation for a number of solutes. Such relation shows that C‐Q patterns of solute export vary from dilution (Ca 2+, Mg 2+, K +, Na +, and Cl − ) to weakly enriching (dissolved organic carbon). The timing of the input imposes a signature on temporal dynamics, most evident for nutrients, and adds uncertainty in the exponent of the C‐Q relation. Key Points: Vertical distribution of solute is a stronger control of concentration‐discharge relation than temporal dynamics of precipitation inputs Solutes of anthropogenic origin show much larger variability than geogenic solutes Numerical experiments help the interpretation of variability in C‐Q relations among solutes